Eradication and control of invasive alien plants in the Mediterranean Basin: towards better coordination to enhance existing initiatives. (16th July 2013) - Brunel, S.; Brundu, G.; Fried, G.
<x xml:space="preserve">Abstract</x> The European and Mediterranean Plant Protection Organization (EPPO), in the framework of its activities in the Mediterranean Basin, launched a questionnaire to gather information on eradication actions and control actions for invasive alien plants. Thirty‐four (34) eradication actions were reported, 16 occurring in Spain, 7 in Italy, 7 in France, 1 in Portugal, 1 in Malta, and 2 on the southern rim of the Mediterranean, with 1 in Israel and 1 in Tunisia. Twenty‐two (22) species were targeted, and the habitats where such actions were undertaken most frequently were coastal dunes, sandy shores and aquatic ecosystems. Most of the species that have been the object of an eradication action were known invasive species recorded in the EPPO lists, such as Ailanthus altissima, Buddleia davidii, Carpobrotus spp., Eichhornia crassipes, Ludwigia peploides, Pennisetum setaceum, Pistia stratiotes, Solanum elaeagnifolium and Sicyos angulatus. Other eradicated species have a limited distribution in the EPPO region and may represent emerging invasive plants, such as Ambrosia confertifolia, Cylindropuntia rosea, Leersia oryzoides, Leptochloa fusca subsp. uninervia and Marsilea drummondii. Control actions concerning 90 species were also reported. A large number of eradication actions, as well as management actions, are therefore happening in Mediterranean countries. At present countries appear to operate with complete autonomy, without consulting neighbouring countries or other stakeholders within the country. There is therefore a need for coordination of new eradication actions.